Uma análise do processo de diversificação da economia angolana partindo do setor agrícola - Miguel, Patrícia Jovita Domingos (2021)
Angola is considered a country rich in mineral and natural resources, but its main source of revenue is the oil sector. At the end of 2014 the country went through an economic recession never seen before, which has dragged on to the present day. This crisis was driven by the fall in the price of a barrel of oil on the international market, which directly affected the country, resulting in a substantial exchange rate crisis. However, diversifying the country's economy and leaving its dependence on the oil sector has been the frequent discourse on the part of the State and one of the top betsis the agricultural sector. Family farming is currently responsible for 90% of national production and 10% of commercial production, but even so the country cannot meet the internal demand for food, with the importation of large quantities of products. Ensuring food security, based on sustainable agriculture and also boosting the sectorfor export, has been a major challenge for the sector today. However, this study soughtto analyze the public programs, developed until then in the context of economic diversification, in order to know how this process has been consolidated and what pathit is on to reach the level of growth expected in the sector. For this, a questionnaire was developed, applied in the first phase to managers of institutions, directly linked to the process of economic diversification linked to the agricultural sector. The second phase was applied to family and commercial producers, as central agents in this process. Through the Grouping Analysis, carried out with data obtained from family and commercial producers, the current state of the sector can be notified, based on the groupings, which were translated into Dendrograms. The sector lacks numerous interventions, since the problems are limiting the sector's long-term advance. Policiesneed better coordination, alignment and engagement, as there is a need to listen moreto producers and really take into account their difficulties, to diversify the production base, create more credit and irrigation policies, bet on research, improvement access roads for production flow, facilitating access to land and creating incentives foragricultural production. These would be some solutions, consolidated in greaterinvestments by the OGE and better alignment in the preparation and execution of programs.